2016
DOI: 10.1016/j.jjcc.2015.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of statin therapy in patients with coronary spasm-induced acute myocardial infarction

Abstract: Statin therapy in patients with coronary spasm-induced AMI with nonobstructive coronary arteries was associated with improved clinical outcome, which was predominantly accounted for by reducing the incidence of myocardial infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 38 publications
(44 reference statements)
1
28
0
Order By: Relevance
“…Additionally, a previous randomized study has demonstrated that statin use suppresses coronary spasm [28]. The results of the present study are in agreement with the previous study [28,29] and support the efficacy and usefulness of statin therapy for coronary spasm after PCI. In this study, smoking was not a predictor of cardiac events related to coronary spasm.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, a previous randomized study has demonstrated that statin use suppresses coronary spasm [28]. The results of the present study are in agreement with the previous study [28,29] and support the efficacy and usefulness of statin therapy for coronary spasm after PCI. In this study, smoking was not a predictor of cardiac events related to coronary spasm.…”
Section: Discussionsupporting
confidence: 92%
“…AMI can be classified into acute ST-segment elevation myocardial infarction (STEMI) and non-ST segment elevation myocardial infarction (NSTEMI). Cardiovascular disease is the most common disease in elderly and also one of the indexes reflecting the prognosis of patients with acute coronary syndrome; aging is an important risk factor of the occurrence and development of coronary heart disease 3,4. Cardiac failure is usually induced after the occurrence of AMI in the elderly.…”
Section: Introductionmentioning
confidence: 99%
“… 50) Statin therapy for spasm-induced AMI patients improved MACE-free survival at 1-year. 51) Statin plus ezetimibe did not significantly reduce MACE compared with high-intensity statin in Korea AMI patients. 52) On subgroup analysis, however, statin plus ezetimibe was effective in high-risk patients, such as those with diabetes mellitus, old age, and low left ventricular ejection fraction (LVEF).…”
Section: Medical Treatmentmentioning
confidence: 90%